The Issue of Microtoponyms in Onomastics - Usmanova, S. A. (European Journal of Life Safety and Stability (2660-9630), 2021)
This article presents macro- and microtoponyms, the views of scientists on this issue, including some microtoponyms in Kokand, their names in the previous, Soviet and independence years.